The Effect of Experiential Marketing on Customer Satisfaction of Cafe Tik Tok in Bengkulu City - Yudi Ariantara (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of experiential marketing on customer satisfaction at Cafe Tik Tok in Bengkulu City. This type of research is descriptive quantitative research to obtain an overview of the effect of experiential marketing strategy on customer satisfaction at Cafe Tik Tok. The t test shows the presence or absence of the influence of one explanatory or independent variable individually in explaining the variation of the dependent variable and is used to determine the presence or absence of the influence of each independent variable individually on the dependent variable tested at a significance level of 0.05 (Ghozali, 2009) . In this study, the first hypothesis is whether there is an influence between Sense (X1) on the Customer Satisfaction variable (Y). To find out whether this hypothesis can be accepted or rejected, a test is carried out using the SPSS version 23 program. The test results for the guarantee variable (Act) show the t-count = 2.513 with a significance value of 0.013 <0.05. With a significance value below 0.05, it indicates that the guarantee (Act) has a significant effect on customer satisfaction. This means that Hypothesis 4 is accepted. The results of the test of the concern variable (Relate) show the value of t count = 2.205 with a significance value of 0.029 <0.05. With a significance value below 0.05, it shows that concern (Relate) has a significant influence on customer satisfaction. This means that Hypothesis 5 is accepted.